Men's disclosure of HIV test results to male primary sex partners. - Schnell, D J (1992)
We evaluated disclosure of human immunodeficiency virus (HIV) antibody status to a main sex partner and the impact on the relationship in men who have sex with men and who are enrolled in the Acquired Immunodeficiency Syndrome (AIDS) Community Demonstration Projects cohorts. Eighty-nine percent of both seronegative and seropositive men disclosed the results to their main sex partner. Seventy percent of the seronegative men and 82% of the seropositive men who did so reported that the relationship remained "as strong as ever" after 6 months. Most men who did not disclose their test results to their main partner reported being "single" after 6 months.